ANALYSIS OF DEVELOPMENT STRATEGY OF TUBAN PUSLATPUR LOCATION TO SUPPORT MARINE TASKS USING SWOT AND ANP METHODS - Sutrisno Sutrisno; Giani Ferianto; I Nengah Putra; I Made Jiwa (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2019)
The Marine Corps Training Command or (Kolatmar) has the main task of carrying out plans and programs for building the capability of the training commands in the Marine Corps. The current problem is that the distance from the marine corps student education center in AAL, KODIKLATAL and PASMAR 2 soldiers in Surabaya is too faraway from Puslatpur in the Situbondo and Banyuwangi areas. The method used in conducting this research was a combination of SWOT Analysis with Analytical Hierarchy Process (ANP). IFE research calculation results were 3.29 while the EFE was 3.08, thus Putlatpur was placed in quadrant II in IE Matrix, the results of weighting strategy were by improving public facilities and supporting facilities of Puslatpur and Puslatpur organizations with support from the central government in increasing the ability of national defense (0.368707), fiscal increase of Indonesian Navy for the development of Puslatpur with support from the central government in enhancing the capability of national defense (0.179934), optimizing Puslatpur coastal's oceanography and logistical support for combat training with ANP processing (with a score of 0.104935), strengthening the legality of Puslatpur locations to avoid socio-cultural impacts in the surrounding community (0.072567), and reducing the socio-cultural impact of the community around the puslatpur with the Navy's strategic policy (0.029992).Keywords- SWOT, AHP, ANP, Internal, External